Analysis of Classroom Interaction in International Class of Chemistry Department at Universitas Negeri Padang - Fuad Nabil Adzanil; Ratmanida Ratmanida (Universitas Negeri Padang, 2022)
The interaction that takes place during classroom activities is crucial in science classes, especially Chemistry because it encourages students' involvement and engagement in the learning process, which promotes students' knowledge during the learning process. Since International Class uses English as the medium of instruction, students are expected to interact in English. However, the non-English department, such as the chemistry department is assumed that there is a tendency for students to avoid interaction in classroom activities because they are afraid of making mistakes, especially when they speak in English. The purpose of the research is to find out how the interactions take place in the learning process and what is the students’ attitude toward classroom interaction. This research involved 27 students of the International Class in Chemistry Department UNP. The design of the research was using descriptive qualitative. Video recordings in the form of transcripts, questionnaires, and interviews were used for the data collection. The data were analyzed qualitatively. The result revealed that the dominating category of each pattern, such as Lecturer-Students indicated the questioning category, Students-Lecturer indicated the response category, and Student-Student indicated the response category. In questioning and explaining the material, the lecturer dominantly used English in the learning process. On the other hand, the students responded to the lecturer’s questions by using Bahasa Indonesia. Moreover, the students showed a positive attitude toward classroom interaction, so the interaction between the lecturer and the students can be implemented in the learning process.